ANALYSIS OF THE SPECIFIC PECULIARITIES OF SOUND SYMBOLISM IN MODERN LINGUISTICS - Alisherova Dilshoda (Galaxy International Interdisciplinary Research Journal, 2023)
Among unmotivated signs, the linguistic sign occupies a special place. Analysis of specific features of sound symbolism in modern linguistics.